2010
DOI: 10.1098/rspb.2010.0433
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in behaviour between the European corn borer,Ostrinia nubilalis, and its sibling speciesOstrinia scapulalis: adaptation to human harvesting?

Abstract: Divergent adaptation to host plant species may be the major mechanism driving speciation and adaptive radiations in phytophagous insects. Host plants can differ intrinsically in a number of attributes, but the role of natural enemies in host plant specialization is often underappreciated. Here, we report behavioural divergence between the European corn borer (ECB, Ostrinia nubilalis) and its sibling species Ostrinia scapulalis, in relation to a major enemy: humans. Harvesting maize imposes selective mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Strong associations were demonstrated among moths using the Z‐pheromone communication system for maize (C4) and the E‐system moths for C3 host plants (Bontemps et al, ; Bourguet et al, ) which were accompanied by significant levels of genetic differentiation (Bethenod et al, ; Malausa et al, ). However, subsequent studies concluded that Ostrinia using the E‐pheromone system in France were O. scapulalis , and a different species compared to sympatric Z‐strain O. nubilalis (Calcagno, Bonhomme, Thomas, Singer, & Bourguet, ; Frolov, Bourguet, & Ponsard, ; Malausa et al, ). Thus, results of these European studies are not directly transferrable to E‐ and Z‐strain O. nubilalis in North America which show significant, but less pronounced and spatially‐dependent associations with C3 and C4 host plants, respectively (O'Rourke et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Strong associations were demonstrated among moths using the Z‐pheromone communication system for maize (C4) and the E‐system moths for C3 host plants (Bontemps et al, ; Bourguet et al, ) which were accompanied by significant levels of genetic differentiation (Bethenod et al, ; Malausa et al, ). However, subsequent studies concluded that Ostrinia using the E‐pheromone system in France were O. scapulalis , and a different species compared to sympatric Z‐strain O. nubilalis (Calcagno, Bonhomme, Thomas, Singer, & Bourguet, ; Frolov, Bourguet, & Ponsard, ; Malausa et al, ). Thus, results of these European studies are not directly transferrable to E‐ and Z‐strain O. nubilalis in North America which show significant, but less pronounced and spatially‐dependent associations with C3 and C4 host plants, respectively (O'Rourke et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These cryptic species might differ in physiological, behavioural and ecological traits (Pfenninger & Schwenk ; Calcagno et al . ; Henry & Wells ). With the application of molecular techniques during the last two decades, cryptic diversity has been detected in almost all taxonomic groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is a slight simplification of Calcagno et al. 's () protocol, our stacks containing seven instead of 11 vials, allowing to monitor more populations while maintaining a similar number of replicates per population.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the vertical movements of ECB and European ABB, Calcagno et al. () found that ECB exhibited positive geotaxis (locomotion towards the ground; Toma, White, Hirsch, & Greenspan, ; Bourguet, Gair, Mattice, & Whitlock, ) in late instars, whereas ABB larvae showed no such behaviour. This behavioural difference translated into contrasted vertical distributions of larvae in the field at the time of harvest.…”
Section: Introductionmentioning
confidence: 99%